2020
DOI: 10.3390/md18100521
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Natural Defenses in Tomato Seedlings by Using Alginate and Oligoalginates Derivatives Extracted from Moroccan Brown Algae

Abstract: Polysaccharides extracted from marine algae have attracted much attention due to their biotechnological applications, including therapeutics, cosmetics, and mainly in agriculture and horticulture as biostimulants, biofertilizers, and stimulators of the natural defenses of plants. This study aimed to evaluate the ability of alginate isolated from Bifurcaria bifurcata from the Moroccan coast and oligoalginates derivatives to stimulate the natural defenses of tomato seedlings. Elicitation was carried out by the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 68 publications
4
15
0
Order By: Relevance
“…Previous works have shown that the ulvan and glucuronan extracted from a green alga, Ulva lactuca, stimulate the natural defenses of tomato [31], olive tree [34] and post-harvest apple [35,36]. Likewise, alginate extracted from the brown algae B. bifurcata, could also stimulate the natural defenses of tomatoes [37] and date palm [29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have shown that the ulvan and glucuronan extracted from a green alga, Ulva lactuca, stimulate the natural defenses of tomato [31], olive tree [34] and post-harvest apple [35,36]. Likewise, alginate extracted from the brown algae B. bifurcata, could also stimulate the natural defenses of tomatoes [37] and date palm [29].…”
Section: Discussionmentioning
confidence: 99%
“…35 Currently, there is more attention for using seaweed extract in horticulture production as part of the crop management program, there are different Seaweeds extract used in different crops while, the use of extracts of brown algae are the major one in the horticultural sector. 36…”
Section: Seaweed Extracts As Plant Biostimulants In Horticulturementioning
confidence: 99%
“…Alginate lyase degrees alginate by β-elimination process to form active oligosaccharides [2]. Alginate oligosaccharides (AOS) are used for a variety of purposes in food, medicine, chemical industry, and agriculture, including cholesterol reduction, antitumor, anti-inflammatory and bacteriostatic, antioxidant, immunity regulation, plant growth promotion, and antiviral materials [3][4][5][6]. Thus, it can be proved that high-activity alginate lyase becomes urgently needed.…”
Section: Introductionmentioning
confidence: 99%